Zur Geschichte des Vereins für Socialpolitik Studien zur Entwicklung der ökonomischen Theorie XLI - Ebner, Alexander (Schriften des Vereins für Socialpolitik, 2023)
»On the History of the ›Verein für Socialpolitik‹«: On the occasion of the founding of the Verein für Socialpolitik 150 years ago, this volume takes up topics of the Association's history. It deals with Gustav Schmoller, leading figure of the Historical School and founder of the Association, with its self-dissolution under National Socialism, and with the debate on Neoliberalism and Social Market Economy. Other topics are the participation of women, the demand for evidence-based economic policy and the changing role of economic history.